Manager Perception of Micro, Small and Medium Enterprises (MSMEs) About Presentation of Financial Statements Based on EMKM Financial Accounting Standards - Syilvana Dwi Novianti (Budapest International Research and Critics University, 2022)
This study aims to determine how the manager perception of micro, small and medium enterprises (MSMEs) regarding the presentation of financial statements based on the EMKM Financial Accounting Standards and identify the factors causing the low perception of MSME managers about the presentation of financial statements based on SAK EMKM. The results showed that the perception of MSME actorsThe results showed the perception of MSME managers with the criteria of Not Good/Low. The factors that cause the perception of MSMEs that are still not good/low are because MSME actors do not understand accounting in running their business, the lack of accounting knowledge they have, so they cannot carry out accounting activities such as recording in ledgers, journals, and making financial reports. Another reason is that MSME actors do not understand the importance of financial reports in running a business and MSMEs do not fully know about SAK EMKM.